Mathematical modeling in MATLAB of a photovoltaic panel. Issue 1 (1st October 2022) - Pop, T; Buzduga, C; Pentiuc, R-D; Ifrim, V-C; Ungureanu, C
Abstract: With the increase in energy demand, the necessity for photovoltaic panels to be as efficient as possible has also increased. In order to achieve the highest possible performance, solar cells depend on a number of environmental elements such as: temperature, shading, cloudy weather, deposits on the surface, dust, solar irradiation, nighttime darkness, etc. All these factors ultimately result in a decline in photovoltaic panels performances. With the help of modeling and simulation programs, complex systems with high performance can be designed and realized, considering the advantage of avoiding manufacturing costs through their physical testing. Based on the electrical and thermal characteristics extracted from the Sanyo producer's data sheet, the proposed commercial photovoltaic module HIT-240HDE4, is implemented in the MATLAB environment under standard and real test conditions. The article presents the modeling and simulation in the MATLAB program of the proposed photovoltaic module, for the analysis of the electrical performances under the described conditions. Also, the article addresses the analysis issue of the operation considering the chosen module, under the same conditions.